Tackling Disinvestment in Health Care Services: the Views of Resource Allocators in the English NHS - Daniels, T.; Williams, Iestyn; Robinson, Suzanne; Spence, K. (Emerald Group Publishing Ltd, 2013)
Purpose – The aims of this paper are to explore the experiences of budget holders within the English National Health Service (NHS), in their attempts to implement programmes of disinvestment, and to consider factors which influence the success (or otherwise) of this activity. Design/methodology/approach – Between 24 January and 15 March 2011 semi-structured, telephone interviews were conducted with representatives of 12 Primary Care Trusts in England. Interviews focussed on: understanding of the term “disinvestment”; current activities, and perceived determinants of successful disinvestment decision making and implementation. Data were organised into themes according to standard qualitative data coding practices. Findings – Findings indicate that experiences of disinvestment are varied and that organisations are currently adopting a range of approaches. There are a number of apparently influential determinants of disinvestment which relate to both health system features and organisational characteristics. According to the experiences of the interviewees, many of the easier disinvestment options have now been taken and more ambitious plans, which require wider engagement and more thorough project management, will be required in the future.Research limitations/implications – Findings from the research suggest that issues around understanding and usage of disinvestment terminology should be addressed and that a more in-depth and ethnographic research agenda will be of most value in moving forward both the theory and practice of disinvestment. Originality/value – This research suggests that, in the English NHS at least, there is a disjuncture between common usage of the term “disinvestment” and the way that it has previously been understood by the wider research community. In addition to this, the research also highlights a broader range of potential determinants of disinvestment than are considered in the extant literature.